Energetics and biomechanics of double poling in regional and high-level cross-country skiers - Zoppirolli, C.; Pellegrini, B.; Bortolan, L.; Schena, F. (European Journal of Applied Physiology, 2015)
Purpose: The aim of this study was to evaluate the energetics and the biomechanics of double poling technique (DP) in two groups of cross-country skiers.